Safe utilization of cultivated land in high-risk areas of soil heavy metal pollution based on soil resilience - Song, Wen; Zhang, Huizhong; Li, Xinju; Song, Hengfei; Niu, Beibei; Shi, Xianjun; Li, Junying (Frontiers in Environmental Science, 2022)
With global urbanization and industrialization, environmental pollution and food safety problems caused by soil heavy metal pollution occur frequently. To realize the safe utilization of cultivated land resources in high-risk areas of heavy metal pollution, we present an approach to safe utilization classification and management in this paper. A typical agricultural area around industrial and mining enterprises located in the economic belt of the Yangtze River Delta was chosen as the research area with cultivated soil as the research object. A total of 1139 geochemical survey sampling sites and soil survey data were used for this research. Initially, the potential ecological risk index was used to assess the potential ecological risk of heavy metals in cultivated soil, and key soil physical and chemical indicators were chosen to assess soil resilience. Next, the safe utilization classification of cultivated land was carried out by combining the potential ecological risk of soil heavy metals with soil resilience. Then, the specific classification management strategy was developed according to ecological risk factor types and crop types. The results showed that the production and operation activities of industrial and mining enterprises in the study area contributed significantly to soil Cd and Hg pollution, and the potential ecological risk of heavy metals in the surrounding soil was high. The soil resilience of cultivated land in the study area was generally not high. The clay content and cation exchange capacity (CEC) were the main strong restrictive indicators, while CaO, soil organic carbon (SOC), and pH were the main medium restrictive indicators. Natural conditions such as topography, hydrogeology, and soil-forming parent material differed by region, resulting in different restrictive factors. There were 16 safe utilization types in the study area. Different management strategies were proposed based on various soil potential ecological risks, soil resilience, ecological risk factor types, and crop types. This study can offer fresh perspectives on the safe utilization classification and management of land resources in high-risk areas of soil pollution, and serve as a reference for sustainable intensification.